RF Imperfections in High-rate Wireless Systems Impact and Digital Compensation - Schenk, Tim.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Wireless communication systems are persistently applying wider bandwidths, larger signal dynamics and higher carrier frequencies to fulfil the demand for higher data rates. This results in an ever increasing demand on the performance of low-cost and power-efficient radio frequency (RF) front-ends. Since the RF technology is, consequently, pushed to its operation boundaries, the intrinsic imperfections of the RF IC technology are more and more governing the system performance of wireless modems. RF Imperfections in High-rate Wireless Systems therefore presents a new vision on the design of wireless communication systems. In this approach the imperfections of the RF front-ends are accepted and digital signal processing algorithms are designed to suppress their impact on system performance. To illustrate this approach, the book focuses on multiple-antenna orthogonal frequency division multiplexing (MIMO OFDM), which will be applied as basis for the majority of near-future high-rate wireless systems. The basics of MIMO OFDM are introduced and the typically required signal processing in the implementation of such systems is elucidated. The book treats several of the front-end impairments that seriously affect the performance of MIMO OFDM systems: carrier frequency offset, phase noise, IQ imbalance and nonlinearities. To provide an in-depth understanding of the impact of these RF imperfections, analytical performance results are presented in the book. These results are then used to design different compensation approaches based on digital baseband processing. RF Imperfections in High-rate Wireless Systems is of interest to wireless system designers, who want to familiarise with the digital compensation of RF imperfections. For researchers in the field of wireless communications this book provides a valuable overview of this emerging research topic. Foreword by Jean-Paul Linnartz.
Multiple-antenna OFDM systems -- Design and implementation of a MIMO OFDM system -- Phase Noise -- IQ Imbalance -- Nonlinearities -- A generalised error model -- Discussion and conclusions.
Keywords: Engineering; Electrical engineering; Microwaves; Optical engineering; Electronic circuits; Engineering; Communications Engineering, Networks; Circuits and Systems; Microwaves, RF and Optical Engineering; Electrical Engineering; Signal, Image and Speech Processing; Electronic books